M-voting in developing countries: Findings from Uganda - Eilu, Emmanuel; Baguma, Rehema; Pettersson, John S. (Commonwealth Governance Handbook, 2014)
In the last two decades, competitive elections have become the standard in a number of African countries. Free and fair elections have not only helped consolidate emerging democratic institutions, but also improved projection for greater economic and political development. In other cases, such as Liberia and Sierra Leone, plausible elections have shaped the route for national reconciliation and a return to democratic rule after years of armed conflict and civil war (CAE, 2009). However, there has been a decline in voter turnout in many developing countries. The African continent has the lowest voter turnout in the world with an average of 65 per cent (Vergne, 2009). The 2005 referendum in Uganda had a voter turnout of only 47 per cent (Petersen, 2006), while, in the 2011 presidential elections in Uganda, more than 40 per cent of the registered 13.5 million voters did not turn up to vote (Oola, 2011; Young, 2005). The reasons for low voter turnout in developing countries range from violence, intimidation and rigging, to voter apathy and election delays (Pande, 2011). Vergne (2009) suggests that this is problematic as low voter turnout creates very weak incentives for politicians to adopt or implement policies in thepublic interest.
Keywords: elections; developing countries; Uganda